2019
DOI: 10.1016/j.jcmgh.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Cystine/Glutamate Antiporter (xCT) Is Required for Chief Cell Plasticity After Gastric Injury

Abstract: Background & Aims Many differentiated epithelial cell types are able to reprogram in response to tissue damage. Although reprogramming represents an important physiological response to injury, the regulation of cellular plasticity is not well understood. Damage to the gastric epithelium initiates reprogramming of zymogenic chief cells into a metaplastic cell lineage known as spasmolytic polypeptide-expressing metaplasia (SPEM). The present study seeks to identify the role of xCT, a cystine/glutama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 51 publications
3
43
0
Order By: Relevance
“…The expression of miR-148a was significantly down-regulated in ImChief cells treated with the inhibitor (Figure 5 B ). Known chief cell and SPEM cell marker expression was examined by quantitative reverse transcription polymerase chain reaction (PCR), and ImChief cells treated with miR-148a inhibitor showed significant up-regulation of the variant 9 splice isoform of Cd44 ( Cd44v9 ), an early marker of SPEM,18, 19 although Tff2 expression was not detected (Figure 5C). The expression of Sox9 and Clusterin ( Clu ), other SPEM-associated markers, was increased, but not significantly (Figure 5 C ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The expression of miR-148a was significantly down-regulated in ImChief cells treated with the inhibitor (Figure 5 B ). Known chief cell and SPEM cell marker expression was examined by quantitative reverse transcription polymerase chain reaction (PCR), and ImChief cells treated with miR-148a inhibitor showed significant up-regulation of the variant 9 splice isoform of Cd44 ( Cd44v9 ), an early marker of SPEM,18, 19 although Tff2 expression was not detected (Figure 5C). The expression of Sox9 and Clusterin ( Clu ), other SPEM-associated markers, was increased, but not significantly (Figure 5 C ).…”
Section: Resultsmentioning
confidence: 99%
“…Chief cell transdifferentiation occurs through coordinated stepwise events, and the process of transdifferentiation can be arrested at different steps. Our group recently showed that inhibition of the cystine transporter xCT by sulfasalazine treatment or xCT knockout arrests chief cell transdifferentiation process and prevents development of SPEM in mouse models of acute oxyntic atrophy 19 . It was also shown that xCT deficiency blocks chief cell transdifferentiation process at a distinct step where the initiating step of Mist1 loss in chief cell reprogramming is not affected, but up-regulation of CD44v9 and autophagy that occur during chief cell transdifferentiation are blocked.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue, 2 groups seek to elucidate some of the metabolic changes that characterize the progression to metaplasia. On one hand, Meyer et al 1 highlight the zymogenic chief cell’s capacity to handle intracellular reactive oxygen species (ROS) as a crucial licensing event during metaplastic reprogramming. Various independent lines of evidence had pointed to the reprogramming of chief cells into a population of proliferative, metaplastic cells as driving epithelial regeneration following glandular injury 2, 3, 4.…”
mentioning
confidence: 99%